My name is Sally Little Song - Woods, Brenda (Brenda A.) (G.P. Putnam's Sons, 2006)
When their owner plans to sell one of them in 1802, twelve-year-old Sally and her family run away from their Georgia plantation to look for both freedom from slavery and a home in Florida with the Seminole Indians.